FLORISTIC FINDINGS OF THE GENUS POTENTILLA L. (ROSACEAE) ON MATERIALS OF THE HERBARIUM OF P.N. KRYLOV (TK) - Kechaykin, Alexey (Acta Biologica Sibirica, 2016)
The article provides new data significantly complement the information on the distribution of nine taxa of the genus Potentilla L. in Asia. Herbarium specimens of these species have been discovered during the study of the genus Potentilla in collections of P.N. Krylov Herbarium (TK, Tomsk, Russia). They are collected at different times in Central Asia, south-eastern part of Western Siberia and Northern Mongolia. The well-preserved and almost intact herbarium specimens were easily definable. After analyzing the relevant available literature we revealed that two species were new for the flora of Kazakhstan – P. chamaeleo Soják and P. stepposa Soják (East Kazakhstan region); one species was new for the flora of Russia – P. penniphylla Soják (south of Siberia, Tuva Republic). For the other six species we found new locations. Of these 6 species, P. blanda Soják is a new species for the flora of Dzhungarian Alatau (Kazakhstan, Almaty region); P. sanquisorba Willd. ex D.F.K. Schltdl. – a new species for Khan Huhe ridge (Mongolia, Uvs aimag);P. turkestanica Soják – a new species for the flora of Tuva Republic. Discovered findings significantly swell the flora of certain regions and botanical and geographical areas. New data on the submitted species can be used by experts in the preparation of specific "Floras" or "Synopsis of Flora" of individual regions. Studied taxa belong to different sections of the genus Potentilla; in the text for each sample we cited the original herbarium label and wrote some notes for all species.